A Bibliometric Analysis of Computational Mapping on Publishing Teaching Science Engineering Using VOSviewer Application and Correlation - Nordin, Nik Abdul Hadi Md (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study was to describe the development of research in the field of teaching science engineering using VOSviewer. This research was conducted by creating a journal database from the Publish or Perish application and managed with the VOSviewer application to classify and visualize the database using the keyword of “Teaching Science Engineering” in the last 10 years (form 2012-2021). A total of 998 articles related to teaching science engineering were analysed and mapped. Based on the mapping results, three terms were obtained, namely “Mathematics” which was associated with 51 links and 335 link strengths; “Engineering Education” associated with 49 links and 146 link strengths; and “Science Technology Engineering Mathematics (STEM)” associated with 48 links and 270 link strengths, respectively. In addition, an analysis of the findings showed that teaching science engineering research in 2012-2016 experienced fluctuating developments. Meanwhile, from 2017 to 2021, teaching science engineering research continues to experience a significant decline. The significant decline in 2019-2021 occurred due to pandemic conditions that impacted the teaching of science engineering related to direct practice in the field. Therefore, it is hoped that the study can help and become a reference for researchers in conducting and determining the research themes to be taken.